Propriedades des fisicas dos Arenitos Caiua. - Campos, J. D. (My University, 1985)
The Caiua Sandstones, sedimentary Cretaceous rocks, have a grain specific gravity nearly that of quartz, its main mineralogical component. The remaining properties, such as the apparent dry density, apparent and effective porosity, water absorption and saturation voids, present high values, but decrease with depth. -from English summary
Physical properties of the Caiua sandstones, Brazil